The Roles of Christ's Humanity in Salvation: Insights from Theodore of Mopsuestia. By Frederick G. McLeod, SJ. Pp. xvi + 278. Washington, DC: The Catholic University of America Press, 2005. ISBN 0 8132 1396 7. 69.95 - Widdicombe, Peter (The journal of theological studies, 2006)
McLeod attempts to set out, and thus to give an apology for, Theodore of Mopsuestia's Christology within the context of what he believes to have been the larger shape of the Antiochene's theology. Identifying Theodore as a ‘literal, historical, and rational’ (p. 28) interpreter of Scripture, concerned with the ‘body’ of the text, McLeod argues that the key to understanding Theodore's thinking about Christ lies in his conception of the roles that typology and the ‘body’ of Christ play in God's plan of salvation. Specifically, Adam in his human nature is a type of Christ in his, and it is through Christ's recapitulation of failed Adam's expression of that nature that that failure and its effects are reversed.